Gendered Political Violence and the Church in Africa: Perspectives from Church Leaders - Ndlovu, James (Religions (Basel, Switzerland ), 2025)
This study investigates the gendered effects of political violence on women (and children) from a church leader perspective. This paper critically examines the role of church leadership in protecting vulnerable groups in society (particularly women and children) and interrogates how church leadership has incorporated women and children into peacebuilding programmes. Using qualitative methods, in-depth interviews were conducted with church leaders affected by political violence in Zimbabwe. The results of this study show that women and children are disproportionately affected by political violence. The women and children are affected socially, economically, and psychologically as a result of political violence, which results in severe trauma, disruption, and loss of livelihoods, and, in severe cases, loss of lives. The results further indicate that the Church plays a crucial role in providing safe havens for the victims, offering spiritual guidance and counselling for the victims. However, the findings show that the Church continues to lack gender sensitivity and inclusivity in peacebuilding programmes. Women and children continue to be underrepresented in leadership roles in churches, as well as in driving the peacebuilding agenda. This paper argues for a transformative and gender-sensitive framework in church-led peace interventions, which prioritises the needs of women and children and incorporates them in the process. This paper argues that by adopting this approach, the Church harnesses its transformative capacity as a change agent for building sustainable peace and addressing political violence in a holistic manner. This interdisciplinary study contributes to the evolving scholarly debates on the intersections of gender, religion, and peacebuilding.